Comorbidities Profile of Psoriasis Patients at Prof. I.G.N.G. Ngoerah General Hospital, Denpasar - Suryawati, Nyoman; Komala, Giorgio Barnes (E-Jurnal Medika Udayana, 2025)
Introduction: Psoriasis, an immune-mediated inflammatory disease, is known to be associated with a range of comorbidities, including arthritis, cardiovascular disease, and psychosocial disorders. Our research focused on understanding the prevalence of comorbidities in psoriasis patients and their implications for treatment and long-term outcomes. Material and methods: This is a cross-sectional–retrospective study conducted at Prof. I.G.N.G. Ngoerah General Hospital from 2018 until 2022. Results: This study included 124 psoriasis patients, ranging in age from 2 to 77 years. The sex distribution was 57.25% males and 42.71% females. Almost all the patients had no comorbidities (71.77%), followed by the patients with one comorbidity (14.51%) and more than one comorbidity (13.70%). The comorbidities of psoriasis patients were dyslipidemia (31.45%), obesity (28.22%), hypertension (16.93%), type 2 diabetes mellitus (12.90%), metabolic syndrome (12.09%), coronary artery disease (4.03%), psychiatric disorder (4.03%), renal disorder (3.22%), and thyroid disease (0.80%). Discussion: This study showed that 28.25% of psoriasis patients have comorbidities, including cardiovascular and metabolic disorders (metabolic syndrome, type 2 diabetes mellitus, dyslipidemia), joint (arthritis psoriasis), and psychiatric disorders. Conclusion: Our findings highlight the necessity of understanding and managing the comorbidities associated with psoriasis, which provides crucial insights for the medical community and patients. Effective comorbid conditions management can enhance psoriasis outcomes and decrease complications.   Keywords : comorbidities, dyslipidemia, hypertension, obesity, psoriasis.